DISPONIBILIDADE HÍDRICA DO SOLO, TAMANHO DE SEMENTE E PROFUNDIDADE DE SEMEADURA NO CRESCIMENTO INICIAL DO MILHO - OLIVEIRA, Camilla Paulino de; BORTOLAZZO, Guilherme; DOURADINHO, Gabriel Zanuto; SILVA, Celi Santana; ZOZ, Tiago (ANAIS DO ENIC, 2018)
-